2020
DOI: 10.1038/s41598-020-61963-7
|View full text |Cite
|
Sign up to set email alerts
|

Neural dynamics of grip and goal integration during the processing of others’ actions with objects: An ERP study

Abstract: Recent behavioural evidence suggests that when processing others' actions, motor acts and goalrelated information both contribute to action recognition. Yet the neuronal mechanisms underlying the dynamic integration of the two action dimensions remain unclear. this study aims to elucidate the eRp components underlying the processing and integration of grip and goal-related information. the electrophysiological activity of 28 adults was recorded during the processing of object-directed action photographs (e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…There is a broad consensus in the research literature that the processing of observed live actions in the AON provides observers with knowledge of what others are doing and that this is a key skill of social cognition [ 8 , 23 , 24 , 25 , 38 , 42 , 43 ]. There is, however, controversy about the properties of the knowledge conveyed by neural AON activities: is this knowledge only provided by AON activities, or is it dependent on conceptual and semantic processing [ 15 , 44 , 45 , 46 , 47 , 48 , 49 ]? Is it primarily related to understanding the goal of actions [ 3 , 5 , 15 ], or does it relate equally to several elements of actions, such as grips, movements of body parts, somatosensory processes, objects involved, or context [ 50 , 51 , 52 ]?…”
Section: Photographs Of Actions: What Makes Them Special Cues To Social Perceptionmentioning
confidence: 99%
See 4 more Smart Citations
“…There is a broad consensus in the research literature that the processing of observed live actions in the AON provides observers with knowledge of what others are doing and that this is a key skill of social cognition [ 8 , 23 , 24 , 25 , 38 , 42 , 43 ]. There is, however, controversy about the properties of the knowledge conveyed by neural AON activities: is this knowledge only provided by AON activities, or is it dependent on conceptual and semantic processing [ 15 , 44 , 45 , 46 , 47 , 48 , 49 ]? Is it primarily related to understanding the goal of actions [ 3 , 5 , 15 ], or does it relate equally to several elements of actions, such as grips, movements of body parts, somatosensory processes, objects involved, or context [ 50 , 51 , 52 ]?…”
Section: Photographs Of Actions: What Makes Them Special Cues To Social Perceptionmentioning
confidence: 99%
“…An observer, for example, sees another individual grasping an apple and understands that the individual wants to eat the apple. Regarding the timing of processing, the findings suggest that an observed grip is associated with an action goal, including information about an object involved or the action context, from around 250 ms after movement onset [ 46 , 105 ]. Processing in the extrastriate body area (EBA), middle temporal area (MT), and inferior parietal regions takes place in the time window of 120 to 200 ms after the movement onset [ 19 , 46 , 106 , 107 , 108 ].…”
Section: Cognitive Products Of Processing Observed Actions In the Aonmentioning
confidence: 99%
See 3 more Smart Citations